The Meaning of Career Orientation on Indonesian Students Who Have Betawi Cultural Background - Fadhallah, R. A. (Universitas Muhammadiyah Metro, 2022)
This research discusses the dynamics of students’ career orientation based on Betawi cultural background. Besides, this study aims to find t he meaning that drives the careers of students who have a Betawi cultural background. The method in this study uses qualitative with phenomenology study. Data collection techniques were carried out by using the interview method with open questions. The respondents were Indonesian students in this case represented by 2018 psychology students of the State University of Jakarta with Betawi cultural background. There were five respondents. The technique used to select the respondents was the purposive sampling technique. Data analysis were done by qualitative analysis techniques, in-depth analysis, and interpretative phenomenological, namely data reduction, presentation, and verification. The results found that the 2018 students of the State University of Jakarta had a socially-oriented career.